Peran Perempuan sebagai Pemimpin dalam Masyarakat Islam : (Studi Ayat-ayat Al-Qur’an tentang Kepemimpinan) - Nadia, Asma; Abdul Syukkur (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
Leadership and women when combined are always two words that can cause controversy. Women’s leadership is a sensitive topic related to the issues of feminism, emancipation and gender issues. Women’s ladership is also a topic that is always interesting, because of the different contexts in which women live, in addition to the different interpretations of religious texts, so that the theme of women’s leadership is never final. This study aims to reveal texts that discuss women’s leadership, due to differences of oponion between whether or not a woman can be a leader. This study uses a qualitative method with a descriptive narrative approach, a type of literature study, and uses a data analysis method using interpretative thematic analysis. The results of the study reveal that a woman is allowed to be a leader, because a women has advantages that are considered capable of leading well.